Strategi Branding Kebon Ndalem Coffee And Eatery Dalam Menarik Minat Beli Konsumen Melalui Media Sosial - Lutfi Hendriyati; Hery Krestanto (STIE Pariwisata API Yogyakarta, 2024)
The purpose of this study aims to: To determine the branding strategy of Kebon Ndalem Coffee and Eatery and To find out how Kebon Ndalem Coffee and Eatery attracts consumer buying interest through social media. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, literature studies and documentation. The results of this study are the branding strategy of Kebon Ndalem Coffee and Eatery, namely Brand Positioning, Brand Identity, Strategy in branding Kebon Ndalem Coffee and Eatery using social media, the aim is to introduce Kebon Ndalem cafe and can increase visits by new guests/customers at this cafe. Social media can increase consumer buying interest, this is in accordance with the opinion of the Head of the Bar Department, Mr. Rizky and the opinions of guests visiting Kebon Ndalem Coffee and Eatery who stated that information about Kebon Ndalem Coffee and Eatery was obtained from Social Media.